2019
DOI: 10.1590/1807-0310/2019v31192956
|View full text |Cite
|
Sign up to set email alerts
|

Involucramiento Político Y Representaciones Sociales De La Democracia en Argentina

Abstract: Este artigo está licenciado sob uma Licença Creative Commons. Com essa licença você pode compartilhar, adaptar, para qualquer fim, desde que atribua a autoria da obra, forneça um link para a licença, e indicar se foram feitas alterações. RESUMEN: el objetivo de este trabajo fue conocer las representaciones sociales (RS) de la democracia en función del involucramiento político. Las RS juegan un rol en la conformación de actitudes y comportamientos y pueden ayudarnos a comprender la reconocida desafección políti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The prospective-ideal dimension, which entails the possibility of positive change, is practically absent in most cases and, when mentioned, is conveyed through citizen participation in unconventional political actions. In a recent study with a population sample from Argentina, we found that traditional political actors and institutions were not relevant to respondents' definition of democracy (Alonso & Brussino, 2018). Instead, procedural aspects, such as voting and elections, and unsophisticated negative qualifying adjectives, such as "bad," "contradictory," and "mediocre," composed the core of their social representations of democracy.…”
Section: The Meaning Of Democracy: a Social Representation Approachmentioning
confidence: 76%
See 4 more Smart Citations
“…The prospective-ideal dimension, which entails the possibility of positive change, is practically absent in most cases and, when mentioned, is conveyed through citizen participation in unconventional political actions. In a recent study with a population sample from Argentina, we found that traditional political actors and institutions were not relevant to respondents' definition of democracy (Alonso & Brussino, 2018). Instead, procedural aspects, such as voting and elections, and unsophisticated negative qualifying adjectives, such as "bad," "contradictory," and "mediocre," composed the core of their social representations of democracy.…”
Section: The Meaning Of Democracy: a Social Representation Approachmentioning
confidence: 76%
“…Evidence from a social representation approach also supports the relevance to political involvement of people's development of democratic orientations (Alonso & Brussino, 2018). Those who participated in politics not only held more positive representations about democracy than those who were not involved but also relied less on the officials and institutions of traditional politics and more on democratic values (e.g., respect, tolerance).…”
Section: Political Capital and The Future Of Democracy In Latin Americamentioning
confidence: 84%
See 3 more Smart Citations